RELASI ANTARA ISAAC ASMOV DAN KARYANYA TRUE LOVE: KAJIAN SOSIOLOGI PENGARANG - Syam, Essy (Universitas Lancang Kuning, 2011)
This writing proves that to understand a literary work completely, the work can not be separated from other elements related to the creation of the work.